Belarus : Transport Sector Policy Note - World Bank (Washington, DC, 2014)
The transport sector is an important economic sector in Belarus, contributing 6.7 percent of Gross Domestic Product (GDP) in 2008 and 6.6 percent in 2009. Belarus has been a net exporter of practically all modes of transport services. The country serves as a transit transport corridor between the European Union (EU) and Russia and potentially between the EU and Asia; thus, the strategic geographical location of Belarus places the country on two of the Pan-European corridors that the EU has committed to promote. In addition to a high geographical concentration of international trade, the trade patterns for specific commodity groups are also concentrated in Belarus. A relatively small number of industrial producers and main export companies dominate the market and generate a corresponding transport demand. The trade logistics environment in Belarus has been improving in many areas. The evolution of freight and passenger transport markets shows that freight traffic movements have grown in line with GDP. Belarus does have the equivalent of a National Transport Strategy and Action Plan. The program for ensuring efficient use of transit potential of the Republic of Belarus for 2006 - 2010, the draft program of the development of transit potential of the Republic of Belarus for 2011 - 2015, and the roads of Belarus program constitute the three key pillars of such a national transport strategy. In addition, the strategy for the development of transit potential of the Republic of Belarus for 2011 - 2015 and the concept of Belarus' transport system development until 2025 have recently been approved by the Government.